Selenium in Oncology: From Chemistry to Clinics - Oliver Micke; Lutz Schomburg; Jens Buentzel; Klaus Kisters; Ralph Muecke (Molecules, 2009)
The essential trace element selenium, which is a crucial cofactor in the most important endogenous antioxidative systems of the human body, is attracting more and more the attention of both laypersons and expert groups. The interest of oncologists mainly focuses in the following clinical aspects: radioprotection of normal tissues, radiosensitizing in malignant tumors, antiedematous effect, prognostic impact of selenium, and effects in primary and secondary cancer prevention. Selenium is a constituent of the small group of selenocysteine-containing selenoproteins and elicits important structural and enzymatic functions. Selenium deficiency has been linked to increased infection risk and adverse mood states. It has been shown to possess cancer-preventive and cytoprotective activities in both animal models and humans. It is well established that Se has a key role in redox regulation and antioxidant function, and hence in membrane integrity, energy metabolism and protection against DNA damage. Recent clinical trials have shown the importance of selenium in clinical oncology. Our own clinical study involving 48 patients suggest that selenium has a positive effect on radiation-associated secondary lymphedema in patients with limb edemas, as well as in the head and neck region, including endolaryngeal edema. Another randomized phase III study of our group was performed to examine the cytoprotective properties of selenium in radiation oncology. The aim was to evaluate whether sodium selenite is able to compensate a preexisting selenium deficiency and to prevent radiation induced diarrhea in adjuvant radiotherapy for pelvic gynecologic malignancies. Through this study, the significant benefits of sodium selenite supplementation with regards to selenium deficiency and radiotherapy induced diarrhea in patients with cervical and uterine cancer has been shown for the first time in a prospective randomized trial. Survival data imply that supplementation with selenium does not interfere with the positive biological effects of radiation treatment and might constitute a valuable adjuvant therapy option especially in marginally supplied individuals. More recently there were emerging concerns coming up from two large clinical prevention trials (NPC, SELECT), that selenium increases the possible risk of developing diabetes type II. Despite obvious flaws of both studies and good counterarguments, a controversial debate remains on the possible advantage and risks of selenium in cancer prevention. However, in the light of the recent clinical trials the potential benefits of selenium supplementation in tumor patients are undeniable, even if further research is needed.